A young teacher exiled in France: Jacinto Luis Guereña (1939-1956) - Guereña, Jean-Louis (Historia y Memoria de la Educación, 2019)
In 1933, Jacinto Luis Guereña, born in Argentina in 1915  of a Basque father and an Italian mother, entered by public examination into the Normal School of Primary Education No. 2 of Madrid (the old Normal School of Teachers). In June of 1936 he finished his theoretical studies, and in the next academic course he was meant to start his internship period as a salaried student-professor. . But the course of historical events, foreseeable for some years, given the strong social tensions existing in the Spain of the 1930s, would completely change the course of his life and ruin virtually all of his legitimate professional and personal dreams. The commitment of the young normalist affiliated to the Students’ University Federation (FUE) after the Franco uprising of July 1936 was clear: he became a militiaman (in the Basque Antifascist Militias), a soldier of the new People's Army of the Republic, a militant of culture and a lieutenant after his time at the Popular School of War for  Engineers. He participated in the battle of the Ebro and after the defeat of the republican offensive remained in Catalonia until the withdrawal. On February 9, 1939, he crossed the border and spent time at several concentration camps in France. The article discusses his professional, cultural and political activities after leaving the camp of Gurs, as well as his attempt to insert himself into French cultural life without losing his Spanish roots. In 1956, when he was again able to enter Spain, he began a new facet of his life, having to make his way into Spanish intellectual life and not only that of exile.